The Gospel of John Marrant: Conjuring Black Christianity in the Black Atlantic. By Alphonso F. SavilleIV . Durham: Duke University Press, 2024. x + 197 pp. 25.95 paper - Russell, Stephen C. (Church history, 2025)
The Gospel of John Marrant: Conjuring Black Christianity in the Black Atlantic. By Alphonso F. SavilleIV . Durham: Duke University Press, 2024. x + 197 pp. 25.95 paper. - Volume 94 Issue 2